If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20w + -27 = -11 + 19w Reorder the terms: -27 + 20w = -11 + 19w Solving -27 + 20w = -11 + 19w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-19w' to each side of the equation. -27 + 20w + -19w = -11 + 19w + -19w Combine like terms: 20w + -19w = 1w -27 + 1w = -11 + 19w + -19w Combine like terms: 19w + -19w = 0 -27 + 1w = -11 + 0 -27 + 1w = -11 Add '27' to each side of the equation. -27 + 27 + 1w = -11 + 27 Combine like terms: -27 + 27 = 0 0 + 1w = -11 + 27 1w = -11 + 27 Combine like terms: -11 + 27 = 16 1w = 16 Divide each side by '1'. w = 16 Simplifying w = 16
| 64.70=4.95+11.95x | | -2y-20=-4-3y | | 6v-2v=24 | | (x+6)(x-6)=28 | | 2v+8-5v=-28 | | 15x-16=33+14x | | 3x=4x+52 | | 16f+23=36+15f | | 5v-15=11+4v | | 2a-5=2a-3 | | 6w-17=27+5w | | 3x+1=5x-12 | | 2.5y+8.4=-20.6 | | 11z-26=-10+10z | | 2(2b-4)-3b=8-4(2-5b) | | 3x+8(2x-6)=2+14 | | A*9fora=2 | | 0.75*5x-x=8.25 | | 10a-9=43+9a | | -7(a-6)=7(a-4) | | -2z+13=45-3z | | -(4b-2)=18-2b | | 10(-5+x)-3=17 | | 3x+5x=30+6 | | -5x+14x=48+24 | | 7(x-3)+4=8x-25 | | 21u-14=0+20u | | K-2=11 | | 2=8x^4+11x^3-9x^2+15x+13 | | 4x-1=7x+9 | | 3x^3+9x^2+4x=0 | | 9(2t-6)=2(3t-9) |